Digital Technology, Perceived Parental Mediation, and Adolescents’ Academic Performance - Korie, Daniel (Advances in Social Sciences Research Journal, 2025)
The intricate relationship between the use of digital technology and academic performance has been a long-standing topic of debate. This study employs a phenomenological approach to investigate adolescents’ lived experiences with digital technology, the role of parental mediation, and the corresponding impacts on their academic performance. Participants included adolescents aged 11 to 18 years (M = 13.5, SD = 3.67) who attended a Boys & Girls Club after-school program in the Southwestern region of the United States. To enhance data triangulation, the study employed a multidimensional qualitative research design that included focus group interviews, individual interviews, and time-use diaries. Results revealed that adolescents’ perceptions and internalization of parental mediation strategies were linked to time management efficacy in digital technology usage. Adolescents with perceived parental co-viewing strategy spent more time using digital technology, followed by active strategy, and restrictive was the third. However, restrictive mediation was found to be a more effective strategy in reducing the potential adverse effects of media technology use on academic performance compared to active and co-viewing strategies. Parental mediation strategies influenced the amount of time adolescents spent on technology, leading to the development of discretionary technology conduct (DTC) and enhancing their academic performance to varying degrees. This study also demonstrates that the timing of technology usage is essential in rendering the existential effects on academic performance inconsequential. Consequently, digital technology neither displaces time for educational activities, as suggested by the displacement hypothesis, nor undermines the academic performance of adolescents.